PERBAIKAN SISTEM KERJA YANG ERGONOMIS UNTUK MENGURANGI KELELAHAN DAN KELUHAN MUSKULOSKELETALDENGAN PENDEKATAN ERGONOMI PARTISIPATOR - Hasti Hasanati Marfuah (Jurnal Ilmiah Dinamika Teknik, 2018)
Fatigue and worker complaints on musculoskeletal is one indication of health and safety disorders. To be able to apply the existing methods in the field of ergonomics can be used participatory approach. The participatory ergonomics approach is used with the aim of providing an opportunity for workers to design and control their systems and working environments with ergonomic ergonomics interventions. In this research, the work system is done by considering the subject factor of the worker, the working envi ronment factor and the working system factor. The result of this research is improvement of work system with participative ergonomic approach which gives decrease of fatigue complaint equal to 21,42%, decrease of musculoskeletal complaint equal to 28,13% and productivity increase equal to 37%. Keywords: Work System, Ergonomics, Participatory, Fatigue, Musculoskeletal Complaints, Productivity